2006
DOI: 10.1107/s0021889806053180
|View full text |Cite
|
Sign up to set email alerts
|

Grazing-incidence small-angle X-ray scattering study of porous dielectrics used in advanced microelectronic interconnections

Abstract: The increase of the integration density and of the operation speed in ultra‐large‐scale integrated microelectronics requires a reduction in the dielectric constant for high‐frequency insulation between the copper connections of some tenth‐of‐micrometre thickness. Recently, the quality of the dielectric has been defined by its dielectric constant k (>1) relative to the unpolarized vacuum (k = 1). Bulk low k will never reach k lower than 3 and the only way to achieve a further decrease in k is to introduce nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…To complement GISAXS experiments, X-ray reflectivity measurements have been performed to characterize the surface morphology and the porous-Si/Si interface roughness generated by the pore front propagation. Simon et al [299] compared GISAXS measurements on nanoporous low-k materials obtained by different routes. They showed that the pore morphology was drastically affected by the process used, ranging from well-defined pore sizes and shapes to ill-defined pores.…”
Section: Porous Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…To complement GISAXS experiments, X-ray reflectivity measurements have been performed to characterize the surface morphology and the porous-Si/Si interface roughness generated by the pore front propagation. Simon et al [299] compared GISAXS measurements on nanoporous low-k materials obtained by different routes. They showed that the pore morphology was drastically affected by the process used, ranging from well-defined pore sizes and shapes to ill-defined pores.…”
Section: Porous Materialsmentioning
confidence: 99%
“…Spin coating and PECVD techniques have been proposed to fabricate pores of nanometric size compatible with the Cu interconnections [299]. In all cases, the SiOCH matrix is mixed with a porogen (organic molecule) removed by a thermal treatment.…”
Section: Low-k and Ultralow-k Nanoporous Dielectric Filmsmentioning
confidence: 99%
“…7,8 The compact films adhere tightly to various substrates with low porosity; nevertheless, it is unsuitable for low dielectric or thermal insulation materials. 9 Electrochemical corrosion-thermal oxidation is a common method for preparing porous SiO 2 insulating films. 10 Kan et al 11 fabricated a thick SiO 2 coating with a porosity of 55−75% from macroporous Si (macro-PS) by electrochemical etching from p-type Si, followed by wet oxidation at 1050 °C; however, the temperature was too high and the fabrication process was relatively complex to be controlled effectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, for many applications in the field of nanotechnology, conventional SAXS performed in transmission geometry suffers from a lack of surface sensitivity. Therefore, grazing incidence SAXS (GISAXS) is in rapid expansion for the characterization of, for example, semiconductor dots (Schmidbauer et al, 1998;Rauscher et al, 1999), metallic islands (Levine et al, 1989;Renaud et al, 2003), implanted materials (Cattaruzza et al, 2000;Babonneau et al, 2006Babonneau et al, , 2007, nanoporous dielectrics (Lee, Park et al, 2005;Simon et al, 2007) and nanocomposite films (Gibaud et al, 2001;Babonneau et al, 2005). GISAXS also generally needs SR since both a small beam size and a high flux are required and, in principle, it can be used in combination with the anomalous technique (AGISAXS).…”
Section: Introductionmentioning
confidence: 99%